The Objective Value of Subjective Value in project design negotiations. Issue 2 (1st October 2016) - Sakhrani, Vivek A.
ABSTRACT: Design in infrastructure public–private partnerships (P3s) involves integrative bargaining. This research looks at the cognitive and psychosocial experience of designers as the dependent variable in such design negotiations. In this study, we associate designers' Subjective Value (SV) outcomes – psychosocial effects such as trust and rapport – with Objective Value (OV) outcomes – economic payoffs of technical design choices. We conducted a design negotiation exercise with treatment and control settings for the conceptual design of a large infrastructure P3 project. Both the public and private participant's objectives were represented in the exercise. The setup tested the effects of two design mechanisms, communication (dialogue) and common knowledge (reduced information asymmetry) on the understanding and SV perceptions of a large number of designers. In particular, we addressed how these designers perceived their understanding of the complex design problem evolve during the design negotiation exercise, and their psychosocial experience of the change in understanding. We also linked their subjective emotional experience to the degree of agreement in design choices. Participants used a real-time tradespace and visualization model to explore and refine designs while negotiating. The tradespace model tracked not only design trials but also every negotiated, agreed upon design outcome. These design choices generated the OV outcomes of negotiated design. Detailed pre-experiment and post-experiment surveys tracked psychosocial and emotive outcomes using an established scale called the Subjective Value Inventory (SVI), as well as other indicator scales. We found that designers overwhelmingly reported high SV scores, which are positively correlated with both their improved understanding of the design problem and their degree of agreement on design choices after the design negotiation. The OV of enhanced psychosocial outcomes, i.e. positive emotive effects, as a result of early stage design negotiations is thus the important relationship foundation for future rounds of engagement between the same actors in long-lived arrangements such as negotiated P3s, especially since P3 participants may not previously have had a history of or opportunities for establishing trust and credibility.